Penerapan Konsep Kaizen Untuk Menurunkan Lead Time Express Maintenance Pada PT Indomobil Trada Nasional Depok - Adiyoso Putro, Ismail (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
Consistency of the quality of a service will affect the survival or lack of such a company inthe needs of a very diverse market, so an effort is needed in the management of the company withcontrol and improvement of quality. Kaizen is one way of continuous improvement that involveseveryone both managers and employees to get optimal results. The purpose of the research is toidentify any obstacles that occur in the process of working on express maintenance as well as tofind the right and good solution to lower lead time in express maintenance. Then kaizen conceptwas applied to lower lead time express maintenance at PT Indomobil Trada Nasional. There aresome problems: the creation of old spare parts, indirect parking fittings, incomplete tools, neatlyarranged tools, and irregular workflows. After improvement, lead time express maintenancedropped from each work, PMS 10,000 KM dropped 8 minutes, PMS 20,000 KM dropped by 12minutes, and PMS 40,000 KM dropped by 4 minutes. As well as the total cost that can betrimmed after kaizen is 3,720,000 rupiah.